DC Sputtering Deposition of Copper Oxide Thin Films Doped with Carbon for Efficient Solar Selective Absorbers - Abdullah, Sawsan H.; Humud, Hammad R.; Mustafa, Falah. I. (Iraqi Journal of Science, 2022)
In this work, carbon-doped copper oxide thin films were deposited by the reactive DC sputtering method for use as selective absorbents. The properties of the DC discharge plasma were studied, using the emission spectrum, in the presence of pure argon and by mixing it with oxygen once and carbon dioxide again to know the effect of adding these gases on the properties of the resulting plasma used in the deposition of films. The structural properties of the deposited thin films prepared with different flow ratio of carbon dioxide gas were studied using x-ray diffraction. To examine the selective absorber coatings, the reflectance within the UV-Vis spectrum was measured to calculate the percentage of energy absorbed by solar radiation using numerical integration. The reflectance was also measured in the range from 2.5 to 25 μm to calculate the thermal emission of the solar heater within a temperature of 373 K. Measurements showed good efficiency as a selective absorption layer. The best absorptance of the solar spectrum (α) was 0.8750, and the lowest emittance (ε) in the infrared region was 0.254 at 25% percentage of carbon dioxide in the reactive gas of the sputtering system. So, this ratio has the highest efficiency as a selective absorber.